2017
DOI: 10.14366/usg.17024
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave elastography in breast ultrasonography: the state of the art

Abstract: Shear-wave elastography (SWE) is a recently developed ultrasound technique that can visualize and measure tissue elasticity. In breast ultrasonography, SWE has been shown to be useful for differentiating benign breast lesions from malignant breast lesions, and it has been suggested that SWE enhances the diagnostic performance of ultrasonography, potentially improving the specificity of conventional ultrasonography using the Breast Imaging Reporting and Data System criteria. More recently, not only has SWE been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 61 publications
6
118
0
4
Order By: Relevance
“…29 Ultrasound (US) imaging is extensively used to assess the elastic properties of tissues. [30][31][32][33][34] Its low cost and relative easy access when compared with magnetic resonance imaging (MRI) could explain its application in different fields of medicine, for example hepatology 30 and mastology. 33 A recent review has specifically addressed the use of US imaging to quantify masseter muscle hardness.…”
Section: A Ss E Ss Ment Of Muscle Hardne Ssmentioning
confidence: 99%
“…29 Ultrasound (US) imaging is extensively used to assess the elastic properties of tissues. [30][31][32][33][34] Its low cost and relative easy access when compared with magnetic resonance imaging (MRI) could explain its application in different fields of medicine, for example hepatology 30 and mastology. 33 A recent review has specifically addressed the use of US imaging to quantify masseter muscle hardness.…”
Section: A Ss E Ss Ment Of Muscle Hardne Ssmentioning
confidence: 99%
“…Also very fibrous breasts with absence of adipose tissue arround can complicate the results. However, sometimes the compression applied can be excessive and we can see an artificial or artefactual stiffness is seen codified into yellow or red color, generally radiating from the skin surface [18].…”
Section: We Can Distinguish Two Types Of Elastographymentioning
confidence: 99%
“…When lesions are harder like cancers, the stiffness area which sorrounds the mass on SWE corresponds in most cases to the echogenic halo identified on B-mode [18,37,38]. When it is too hard to propagate the shear wave the central area of the lesion and appears without a color code [17,37].…”
Section: E Score 5 (E5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, shear wave elastography (SWE) recently has become available on multiple systems and is attractive due to its 2D imaging capability and quantitative nature. Because of the unique tissue mechanical information provided, numerous clinical studies have demonstrated the clinical utility of ultrasound elastography, such as in liver, breast, prostate, kidney, pancreas, and musculoskeletal (MSK) applications 6, 7, 8, 9, 10, 11. For example, 2D SWE was shown to have high sensitivity in the assessment of liver fibrosis 12.…”
Section: Introductionmentioning
confidence: 99%